SHORTFALL IN INCOMES OF A REGIONAL GAS DISTRIBUTION ORGANIZATION: ANALYSIS AND MODELLING - N. Yu. Lebedeva; A. V. Mitrofanova (Вестник университета)
The problem of generating shortfall in incomes in a gas distribution organization as a result of changes in the state`s institutional standards has been considered. Shortfall in incomes exacerbate the problem of a shortage of investment resources directed by a territorial organization to develop distribution networks. Thereby it has a negative impact on the region’s infrastructure development and on population’s life quality, especially rural population. The main part of the study has been made up of a comprehensive analysis of the shortfall in incomes of a gas distribution organization during 2015-2017, the process of their creation is described. Two methods for pricing shortfall in income: the existing order of calculation and the fixed-cost method have been compared. To estimate the shortfall in incomes elasticity by the connection number for individuals with the gas pipeline-inputs construction, a correlation-regression model has been built that has a high degree of reliability. This model can be used by an enterprise during the operational planning process. It has been concluded, that overcoming the growth tendency of shortfall in incomes is possible by reducing the balance value of the facility. Therefore, further research in this area should be aimed at finding ways to reduce the production cost.